The missing discipline behind failure to scale : companies make significant investments in developing and incubating new business initiatives, but too few follow a rigorous path to scaling their ventures - Binns, Andy; Griffin, Christine (MIT Sloan Management Review, 2023)
Only 16% of new corporate ventures succeed, mainly because there are few methodologies for reaching scale. The authors’ research shows that successful companies use scaling paths. Such paths require a clarity of ambition; an understanding of the assets needed to access customers, capabilities, and capacity; and a willingness to use a variety of techniques to assemble those assets into a coherent strategy for attaining scale. This article offers leaders five lessons for blazing a scaling path.